The use of knowledge map model in construction industry - Tserng, H. Ping; Yin, Samuel Yen-Liang; Lee, Meng-Hsueh (Journal of Civil Engineering and Management, 2010)
The construction industry consists of many unstructured documents, which accumulate a large volume of tacit knowledge. In the general domain, a Knowledge Map can illustrate connections of knowledge and transfer tacit knowledge to explicit knowledge, but this is unsuitable on specific domain such as construction industry. This research generalized existing mapping rules to be applied to general and specific domain; and presented a novel and practical model for building knowledge map, named Knowledge Map Model (KMM). This model comprised of five procedures, including identifying problems, discussing with experts and users, establishing the classification structure, establishing the document base, and deciding the display model. Furthermore, this research establishes Knowledge Map Model System (KMMS) as a major tool to improve the knowledge map reused and shared among the practical process. Finally, this re‐search validated the KMM in a real project of bridge maintenance.First Published Online: 10 Feb 2011